การเปรียบเทียบผลการระงับปวดหลังผ่าตัดระหว่างวิธีการฝังเข็มแบบกระตุ้นไฟฟ้า และทรามาดอลไฮโดรคลอไรด์ในสุนัขภายหลังการศัลยกรรมทำหมันเพศเมีย - ปราณิศา มหัตนิรันดร์กุล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Acupuncture is one of the Traditional Chinese Medicine treatment technique commonly used in practice, especially for pain control. This study compared the postoperative analgesics effects between electroacupuncture and tramadol HCl in dogs subjected to ovariohysterectomy. Twelve female mixed-breed dogs subjected to ovariohysteractomy were used in this study. The dogs were divided into 2 groups. 1.) Acupuncture group (n=6), the dogs were treated with low frequency 2 Hz electroacupuncture at acupoints Stomach 36 (ST-36) and Large Intestine 4 (LI-4) before an initiation of the surgery. Stimulation of acupoints Governing Vessel 20 (GV-20) was performed by manual twitching every 10 minutes. 2.) Medicine group (n=6), the dogs were treated with subcutaneous injection of tramadol HCl at the dosage of 4 mg/kg before surgery. Data of the vital signs, sedation score, cumulative pain score, and skin pressure threshold measuring with algometer were evaluated at pre-operation and 1, 3, 6, 12, and 24 hours post-operation. The comparison between both groups indicated that sedation score of medicine group was significantly (p≤0.05) higher than acupuncture group at 1 hours post-operative. The results also indicated that there were no statistically difference in vital signs, cumulative pain score, and percentage change of skin pressure threshold within 24 hours post-operation between these two groups. The percentage change of pressure threshold at 24 hours post-operation of acupuncture group and medicine group was 31.67% and 40.71%, respectively. According to the results of this study, preoperative treatment with electroacupuncture and tramadol HCl for the dogs subjected to ovariohysterectomy produced similar postoperative analgesics effects during the first 24 hours after the surgery.